Mesenchymal stem cells and the lung. Issue 3 (21st March 2013) - Sinclair, Kenneth; Yerkovich, Stephanie T.; Chambers, Daniel C.
Abstract: Mesenchymal stem cells (MSC) are a population of tissue‐resident adult progenitor cells that were originally identified in bone marrow, but have now been identified in many organs including the lung. Although their precise role in organ function remains incompletely defined, mounting evidence suggests that they are an important component of the parenchymal progenitor cell niche and orchestrate organ homeostasis and repair following injury. In this review, what is known about MSC biology will be outlined with particular emphasis on lung biology, and the therapeutic potential of MSC‐based cell therapy will also be highlighted.